Executive Decision-Making through Simulation (Book). - Zeff, Stephen A.; Bruns, William J. (The Accounting Review, 1966)
Reviews the book "Executive Decision Making Through Simulation," by Douglas C. Basil, Paul R. Cone and John A. Fleming.